Assessing Urban Rail Service Quality and User Satisfaction: A PLS-SEM Study on LRT Jabodebek in Jakarta Metropolitan Region - Adil Afrizal Gani; R. Jachrizal Sumabrata; Sutanto Soehodho (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2026)
Light Rail Transit (LRT) Jabodebek was developed to improve urban mobility and promote a shift from private vehicles to public transportation. However, understanding of the service quality dimensions that most influence user satisfaction remains limited. This study aims to analyze the effect of accessibility, comfort, punctuality, safety, and information on user satisfaction of LRT Jabodebek. The study employed a quantitative approach using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method based on survey data from 300 users on the Harjamukti-Dukuh Atas and Jatimulya-Dukuh Atas corridors. The results of the analysis indicate that the measurement model meets the criteria of reliability and validity. Furthermore, the structural model shows that accessibility (β = 0.35; p < 0.001), comfort (β = 0.31; p < 0.001), punctuality (β = 0.27; p = 0.002), safety (β = 0.22; p = 0.007), and information (β = 0.18; p = 0.034) have a positive and significant effect on user satisfaction. The accessibility variable exerts the greatest influence on user satisfaction. The coefficient of determination (R² = 0.64) indicates that the model is able to explain 64% of the variation in LRT Jabodebek user satisfaction. This study provides an empirical contribution by developing a comprehensive model of urban rail service quality using the PLS-SEM approach in the context of LRT Jabodebek. These findings offer practical implications for operators and policymakers to prioritize improvements in accessibility, comfort, punctuality, safety, and information quality in order to enhance user satisfaction and promote more sustainable public transportation use.